Estudo do gênero: uma abordagem do estilo no livro didático de língua portuguesa do ensino médio - Nascimento, Terezinha de Jesus Gomes do (2016)
The expository approach to linguistic and extralinguistic elements is essential for understanding the genres of discursive perspective. The style is one of the foundations of its architectural, responsible for the construction of meaning and expressiveness characteristic of the genre. For this reason, this research seeks to analyze the texts style approach: chronic, popular science text, drive letter and writing exam, taken in a dialogic perspective in "Working the genre " section of the textbook for high school "Portuguese languages" William Cereja and Thereza Magalhães (2013). It is argued that the style of study, taken as a dialogical aspect, contributes significantly to the understanding of language development employees in genres, contributing to a careful reading and written production more creative. Qualitative-interpretative nature, research is founded on assumptions of Bakhtin and the Circle and several other scholars of Bakhtinian reflections. The results show the systematization of activities proposed in the textbook from PNLD guidelines (2015), the dissonance between theories behind the work with genders, employing the concepts of genre and discursive genre indiscriminately. In addition, the manual distance is a style approach addressing the expressiveness and sense of language choices enunciator, evidenced in the analyzed texts, presenting many gaps in this perspective could be exploited. It is clear that the textbook is not solely responsible for reading and writing improvement of students. However, we expect that this material promotes the genre style of teaching in a discursive perspective, essential for improving the use of language. Working with the style of the genre requires greater attention from researchers, considering that this is one of the most important elements in the constitution of the texts.